Dynamics of fermentation quality, bacterial communities, and fermentation weight loss during fermentation of sweet sorghum silage - Haiwen Xu; Nier Wu; Na Na; Haijun Ding; Lin Sun; Yongyu Fang; Dongyang Li; E Li; Baozhu Yang; Xiaobin Wei; Yanlin Xue (BMC Microbiology)
Abstract Background Sweet sorghum is used mainly as an energy crop and feed crop in arid and semiarid regions, and ensiling is a satisfactory method for preserving high-quality sweet sorghum. The aim of this study was to reveal the dynamics of the fermentation quality, bacterial communities, and fermentation weight loss (FWL) of sweet sorghum silage during fermentation. Methods Sweet sorghum was harvested at the first inflorescence spikelet stage and ensiled without (CK) or with lactic acid bacterial (LAB) additives (L). After ensiling, samples were collected on days 0, 1, 3, 5, 15, 40, and 100 to assess the fermentation quality, bacterial communities, and FWL. Results For CK and L, on day 1, the pH was 5.77 and 5.57, respectively, and the lactic acid (LA) was 1.30 and 2.81 g/kg dry matter (DM), respectively. Compared with CK, L had a lower pH and higher LA from days 1 to 5 (P < 0.05), a lower FWL from days 5 to 100 (P < 0.05), and a greater abundance of Lactiplantibacillus from days 1 to 15 (P < 0.05). The main bacterial genera were Leuconostoc and Weissella in CK and Lactiplantibacillus, Leuconostoc, and Weissella in L on day 1; Lactiplantibacillus in all silages from days 3 to 40; and Lactiplantibacillus and Lentilactobacillus in all silages on day 100. Conclusions Sweet sorghum silage fermented relatively slowly during the first day. Moreover, inoculation with LAB accelerated fermentation and optimized bacterial communities during the initial fermentation phase. Inoculation with LAB also reduced the silage FWL, and the LAB succession relay occurred in the silage throughout the fermentation process.